2020
DOI: 10.1186/s12877-020-01860-w
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sarcopenia prevalence between upper-body and lower-body based EWGSOP2 muscle strength criteria: the Tromsø study 2015–2016

Abstract: Background The European Working Group on Sarcopenia in Older People (EWGSOP2) recommends grip strength and chair stand tests to be used as primary defining measures. It is unclear how either test affects prevalence estimates. Methods This cross-sectional study involved 3498 community-dwelling participants (40–84 years) from the 7th Tromsø Study survey (2015–2016). We used grip strength, five-repetition chair stands, four-meter Walk Speed Test, Timed-Up-and-Go (TUG) and Dual-Energy X-ray Absorptiometry measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
7
29
0
Order By: Relevance
“…27 Additionally, we did not include data to investigate the successive step of confirmed sarcopenia in the EWGSOP2 algorithm, as our previous study indicates that a low number of participants qualified for this criterion. 37 It would be of interest to explore whether similar associations as found in the current study also exist for participants who additionally express low lean mass. Nonetheless, it is clear that muscle strength is becoming more emphasized, and lean mass less so, as sarcopenia definitions continue to develop.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…27 Additionally, we did not include data to investigate the successive step of confirmed sarcopenia in the EWGSOP2 algorithm, as our previous study indicates that a low number of participants qualified for this criterion. 37 It would be of interest to explore whether similar associations as found in the current study also exist for participants who additionally express low lean mass. Nonetheless, it is clear that muscle strength is becoming more emphasized, and lean mass less so, as sarcopenia definitions continue to develop.…”
Section: Discussionsupporting
confidence: 60%
“…However, roughly 65% of participants achieved the newly updated WHO physical activity recommendations of 150 min non‐bouted MVPA per week, indicating that the current cut‐points were relevant for our study sample of older adults 27 . Additionally, we did not include data to investigate the successive step of confirmed sarcopenia in the EWGSOP2 algorithm, as our previous study indicates that a low number of participants qualified for this criterion 37 . It would be of interest to explore whether similar associations as found in the current study also exist for participants who additionally express low lean mass.…”
Section: Discussionmentioning
confidence: 87%
“…Chair stand score decreased by age and, among women, increased by height and weight. A similar age pattern was found in several studies [ 23 , 28 , 36 ] whereas only one study addressed variation by anthropometric variables and found an increase by weight but no variation by height [ 25 ].…”
Section: Discussionsupporting
confidence: 78%
“…While other studies also found an association between a high risk of malnutrition and lower muscle mass but not with lower muscle strength [45e47]; others did show an association between malnutrition and muscle strength [47e50]. According to the EWGSOP2, muscle strength can be determined by handgrip strength or by the chair stand test but poor agreement has been shown between upper-and lower measures of muscle strength in older adults [51,52], also resulting in different prevalence rates of sarcopenia [53]. Future research should assess the adequacy and agreement between measures of muscle strength to diagnose sarcopenia in geriatric rehabilitation.…”
Section: Association Between Malnutrition and Sarcopenia Stagesmentioning
confidence: 99%